Academic inbreeding and isolation in South African psychology - Fouché, Jan; Louw, Dap (University of the Free State, 2001)
Several factors have contributed to the fact that academic inbreeding and isolation have reached almost epidemic proportions at South African universities. Although this phenomenon has been described as a cancer in tertiary education, almost no data are available regarding the specific prevalence of inbreeding and isolation in academic psychology in South Africa. The present study aims to make a contribution in this regard. More than 1 000 questionnaires were distributed to academics and professionals to determine how many of them have obtained their qualifications from a single university; whether they were, at the time of the study, employed at a university from which they had graduated; what overseas training they had had; how many were members of international psychological associations; their attitudes towards continuing education, and to what extent they utilised computer networks. The findings are presented and recommendations made.

Verskeie faktore het daartoe bygedra dat akademiese inteling en isolasie feitlik epidemiese afmetings by Suid-Afrikaanse universiteite aangeneem het. Hoewel hierdie verskynsel beskryf word as ’n kanker in tersiêre onderwys, is feitlik geen data beskikbaar rakende die spesifieke omvang van inteling en isolasie in akademiese sielkunde in Suid-Afrika nie. Die huidige studie het daarom ten doel om ’n bydrae in hierdie verband te maak. Meer as 1 000 vraelyste is versprei om vas te stel watter hoeveelheid akademici hul sielkundekwalifikasies by slegs een universiteit ontvang het, of die akademikus werksaam was by die Universiteit waar hy of sy ’n graad verwerf het, in welke mate akademici buitelandse opleiding ontvang het, hoeveel akademici lede is van internasionale sielkundeverenigings, wat hul houding jeens voortgesette opleiding is, en in watter mate hulle van rekenaarnetwerke gebruik maak. Die bevindings word aangebied en aanbevelings word gemaak.
Keywords: Academic inbreeding; South African universities; Academic psychology; Inbreeding and isolation